Comprehensive Evidence-Based Assessment and Prioritization of Potential Antidiabetic Medicinal Plants: A Case Study from Canadian Eastern James Bay Cree Traditional Medicine. (20th December 2011) - Haddad, Pierre S.; Musallam, Lina; Martineau, Louis C.; Harris, Cory; Lavoie, Louis; Arnason, John T.; Foster, Brian; Bennett, Steffany; Johns, Timothy; Cuerrier, Alain; Coon Come, Emma; Coon Come, Rene; et al.
Abstract : Canadian Aboriginals, like others globally, suffer from disproportionately high rates of diabetes. A comprehensive evidence-based approach was therefore developed to study potential antidiabetic medicinal plants stemming from Canadian Aboriginal Traditional Medicine to provide culturally adapted complementary and alternative treatment options. Key elements of pathophysiology of diabetes and of related contemporary drug therapy are presented to highlight relevant cellular and molecular targets for medicinal plants. Potential antidiabetic plants were identified using a novel ethnobotanical method based on a set of diabetes symptoms. The most promising species were screened for primary (glucose-lowering) and secondary (toxicity, drug interactions, complications) antidiabetic activity by using a comprehensive platform of in vitro cell-based and cell-free bioassays. The most active species were studied further for their mechanism of action and their active principles identified though bioassay-guided fractionation. Biological activity of key species was confirmed in animal models of diabetes. These in vitro and in vivo findings are the basis for evidence-based prioritization of antidiabetic plants. In parallel, plants were also prioritized by Cree Elders and healers according to their Traditional Medicine paradigm. This case study highlights the convergence of modern science and Traditional Medicine while providing a model that can be adapted to other Aboriginal realities worldwide.